2021
DOI: 10.31290/jpk.v10i1.2027
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Dukungan Keluarga Dengan Pola Pemberian Asi Pada Bayi Usia 0-6 Bulan

Abstract: Air Susu Ibu atau ASI memiliki banyak kandungan yang penting untuk tumbuh kembang anak. Pola pemberian ASI dibedakan menjadi eklslusif dan tidak eklslusif. Perilaku seseorang dalam pemberian ASI dipengaruhi oleh berbagai faktor pembentuk perilaku kesehatan salah satunya yaitu dukungan keluarga. Studi literatur ini bertujuan untuk mengetahui hubungan dukungan keluarga dengan pola pemberian ASI pada bayi usia 0 sampai dengan 6 bulan. Metode penulisan karya ilmiah ini menggunakan studi literatur. Sumber pustaka m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In the study of Bajoulvand et al, the perceived power structure was recognised as the best predictor of exclusive breastfeeding behaviour intention due to the research time during the breastfeeding period [27]. Although the support of family members, friends and healthcare personnel leads to an increase in the intention of exclusive breastfeeding behaviour, there was no significant relationship with intention and behaviour in this study [22,32,[49][50][51]. Interestingly, according to a study by Fabiyi et al, the lack of support from health workers for EBF by pregnant mothers is more effective in discouraging them than the views of other people [52].…”
Section: Discussionmentioning
confidence: 60%
“…In the study of Bajoulvand et al, the perceived power structure was recognised as the best predictor of exclusive breastfeeding behaviour intention due to the research time during the breastfeeding period [27]. Although the support of family members, friends and healthcare personnel leads to an increase in the intention of exclusive breastfeeding behaviour, there was no significant relationship with intention and behaviour in this study [22,32,[49][50][51]. Interestingly, according to a study by Fabiyi et al, the lack of support from health workers for EBF by pregnant mothers is more effective in discouraging them than the views of other people [52].…”
Section: Discussionmentioning
confidence: 60%
“…The findings of this study were consistent with research conducted by (Oyay et al, 2020) in Kampung Sereh, Sentani Health Center in Papua, using a case-control study design, which found a link between biological mothers' support for breastfeeding mothers and the practice of exclusive breastfeeding. The study was carried out by (Supriyanto et al, 2021), and the research method used was qualitative. Secondary data obtained from previous research articles and journals or from appropriate internet sites were used in the study.…”
Section: The Influence Of Parental Social Supportmentioning
confidence: 99%